Commercial Sexual Behaviors Among Male Rural-to-Urban Migrants in Western China: Implications for HIV Prevention. (July 2017) - Li, Wenwei; Jiang, Junjun; Su, Jinming; Liang, Bingyu; Deng, Wei; Huang, Jiegang; Qin, Bo; Upur, Halmurat; Zhong, Chaohui; Wang, Qianqiu; Wang, Qian; Zang, Ning; et al.
Rural-to-urban migrants are at high risk of HIV infection. The goal of this survey was to explore the commercial sexual behavior and condom use among male rural-to-urban migrants in western China. A cross-sectional survey on male rural-to-urban migrants in western China was conducted. Among all the subjects surveyed, 140 (7.4%) had commercial sexual behavior, which is associated with being aged older than 24 years, being of Han or other ethnic minorities, being divorced, separated, or widowed, having experienced drug abuse, having had heterosexual behavior, having had casual sexual partners, having had sex with a homosexual, and being from Xinjiang. A total of 31.4% of them never use condoms when buying sex. Not using condoms is associated with being from Chongqing, having a high school or above education, and having commercial sex monthly. Commercial sexual behavior and not using condoms are common among male rural-to-urban migrants in western China. Strategies and appropriate education should be developed to prevent HIV transmission due to high-risk sexual behaviors.